Recent advances in developing 3D culture systems of spermatogonial stem cell preservation and differentiation: A narrative review - Leyla Fath-Bayati; Leila Naserpour; Mohadeseh Khoshandam; Rahil Jannatifar; Hoda Fazaeli (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Male infertility has received vast attention in recent years and has no clear etiology in almost 40% of cases. Several methods have been suggested for preserving sperm and spermatogonial stem cells (SSCs) in both in vivo and in vitro conditions. The efficacy of these methods is related to their abilities, including providing an optimal environment for sperm preservation and long-term SSC culture for in vivo and in vitro differentiation of these cells. In this review article, a full MEDLINE/PubMed search was performed using the following search terms: "Spermatogonial Progenitor Cells, Stem Cells, Fertility Preservations, Sperm Freezing, Cell Differentiations, Tissue Scaffold, 3-Dimensional Cell Culture", which retrieved results from 1973-2022. Related articles were added to the bibliography of selected articles. Exclusion criteria included non-English language, abstract only, and unrelated articles. The production of functioning male germ cells is suggested by introducing modern bioengineered systems as a new hope for the maintenance of male fertility. Till now, few in vitro spermatogenesis investigations have provided appreciable amounts of mature gametes. Each method had benefits and disadvantages, but the 3-dimensional culture method had the greatest impact on the differentiation and preservation of SSCs. One of the critical elements of research is the preservation of sperm and the differentiation of SSCs. Several methods have been employed in this area. Various scaffolds providing an environment similar to an extracellular matrix and conditions for germ cell development and survival have been employed in recent research.